ANALISIS SISTEM PEMBERIAN KREDIT PROGRAM KEMITRAAN BINA LINGKUNGAN DI PT JASA RAHARJA PERSERO SULUT - Kaunang, Jessica Ch; Sabijono, Harijanto; Wangkar, Anneke (JURNAL RISET AKUNTANSI GOING CONCERN, 2017)
Development in the field of economics is an objective to be achieved in implementing economic development programs,including the partnership program implemented by state enterprises to small businesses. The partneship program is a CSR program of SOEs as a concern to the community. This research done on the basis of program Kemitraan Bina Lingkungan (PKBL) conducted by PT Jasa Raharja Persero Manado, that aims to prevent the occurrence of non performing loans for micro and small business credit. The kind of research used is descriptitive qualitative. Preventive measures undertaken doing by visiting for every three months.Keywords: System and procedure of credit, micro and small business credit, Non performing loans.